Tantangan & Upaya Kepala Sekolah Dalam Meningkatkan Supervisi Pendidikan Di SD It Al Munadi Marelan - Aina ul mardiyah Ray; Aidatu Fauziah; Imas ayu Salamah; Ari Wibowo; Syilvi Marsela diastami (Pusat Riset dan Inovasi Nasional, 2023)
The principal is one of the key factors in determining the quality of education. Referring to its functions and roles, the principal functions as the manager and leader of the school education institution. Effective management and leadership requires principals who embody modeling and transformational leadership, demonstrated by characteristics such as ideal influence, motivational inspiration, intellectual stimulation and individual consideration. This is the challenge for school principals to manage change well for the sake of sustainability and continuous improvement of school quality. They must empower teaching staff, work under clear time frames, build interpersonal relationships, develop fairness and principles of accountability, and be able to work in teams.